A proteção da privacidade no contexto de regulação da inteligência artificial - Vilela, Naiara Aparecida Lima (2024)
With the advancement of technology, several realities in society have been transformed. Among them, one promises a significant transformation in the social environment, artificial intelligence technology. Among so many points of attention that can be questioned, privacy is a very significant topic, considering that for an intelligent system to work it requires data, including personal data, which can lead to mitigation of the right to privacy. Furthermore, data and algorithms can influence both the collective and the individual, as well as cause discrimination and bias. In this way, the artificial intelligence system takes precautions and necessary regulation to protect human beings from possible harm. Thus, at the heart of this research, privacy protection will be addressed in the context of regulating artificial intelligence, since the standards already in place for the protection of personal data may not be sufficient or even not very inclusive, not encompassing the reality of artificial intelligence. In this sense, as specific objectives, the nature of this technology will be examined, as well as the data-based economy and the surveillance society, as well as the effective protection of the right to privacy, in order to observe how the guarantee of this right occurs in different protective plans. In this sense, using the methodology of bibliographical review and the deductive method, it was concluded that an ideology of digital constitutionalism meditates on the image of protection in different sectors, given that the Law may not be able to meet the constant and rapid evolution of technology now studied, thus also leading to regulated self-regulation.